High‐Performance Photothermal Conversion of Narrow‐Bandgap Ti2O3 Nanoparticles. Issue 3 (11th November 2016) - Wang, Juan; Li, Yangyang; Deng, Lin; Wei, Nini; Weng, Yakui; Dong, Shuai; Qi, Dianpeng; Qiu, Jun; Chen, Xiaodong; Wu, Tom
Abstract : Ti2 O3 nanoparticles with high performance of photothermal conversion are demonstrated for the first time. Benefiting from the nanosize and narrow‐bandgap features, the Ti2 O3 nanoparticles possess strong light absorption and nearly 100% internal solar–thermal conversion efficiency. Furthermore, Ti2 O3 ‐nanoparticle‐based thin film shows potential use in seawater desalination and purification.